Dynamic changes in the metabolite profile and taste characteristics of Fu brick tea during the manufacturing process. (15th May 2021) - Li, Qin; Jin, Youlan; Jiang, Ronggang; Xu, Yongquan; Zhang, Yiyang; Luo, Yu; Huang, Jianan; Wang, Kunbo; Liu, Zhonghua
Graphical abstract: Highlights: Metabolite and taste characteristic variation during tea processing were clarified. Relationship between metabolite and taste attributes was exhibited. Core functional microorganisms linked to the metabolic variations were identified. Abstract: Fu brick tea is a typical post-fermentation tea known for its special flavor and health benefits. Liquid chromatography-mass spectrometry, and sensory evaluation with multivariate analysis were used to characterize the dynamic changes in metabolite profile and taste characteristics. Seventy-one compounds were identified as critical metabolites, catechins, flavonoids, phenolic acids, terpenoids and others. During the manufacturing process, these compounds exhibited sharp fluctuations in content, the intensities of astringency, bitterness, and sourness of the tea materials reduced greatly, but the mellow intensity increased sharply. Several catechins and phenolic acids were positively related to the 'astringent', 'bitter', and 'sour' tastes attributes. The fungal genera, Aspergillus, Candida, unclassified_o_Hypocreales, unclassified_o_Saccharomycetales and Wallemia and the bacterial genus, Klebsiella, were identified as core functional microorganisms linked to the metabolic variations during the process. Overall, these findings provided a more comprehensive understanding of the formation of the sensory characteristics in Fu brick tea during the manufacturing process.